How do private practitioners in Pakistan manage children suspected having tuberculosis? A cross sectional study - Yaqoob, Aashifa; Hinderaker, Sven Gudmund; Fatima, Razia; Najmi, Hina; Anwar-ul-Haq (BMC public health, 2021)
In Pakistan, private providers provide a large portion of health care, including for tuberculosis (TB). All TB patients are supposed to be reported to the National Tuberculosis Program (NTP), which provides drugs free of charge in addition to monitoring, supervision, and support. However, diagnosis of TB in children is difficult. We aimed to assess the private health care providers' investigation practices and management of childhood TB. We used a cross-sectional study, which was based on a national survey measuring under-reporting of children with TB in 12 selected districts in Pakistan from April-June, 2016. We explored the practices of the private health care providers, including the health care workers i.e. general practitioners, pediatricians, pulmonologists and chest specialists, who were involved in the diagnosis of TB in children under 15 years for investigating and managing children suspected having TB. Among 6519 presumptive child TB cases, a total of 5193(79.7%) children under 15 years were diagnosed as TB by private health care providers during second quarter, 2016. Only 187(2.9%) were notified to NTP. The majority of presumptive child TB cases reported cough, fever, and failure to thrive; few had TB contacts with pulmonary TB patients. Failure to thrive, loss of body weight and absence of BCG (Bacillus Calmette-Guérin) scar was more common in female children. Private providers relied on chest X-ray in 46.1%, while tuberculin skin test and Gene-Xpert MTB/RIF testing was little utilized. Bacteriological confirmation was present in 7.6%, and clinical assessment was the only basis for diagnosis in 39.3%. Of children with presumptive TB, only 955(14.6%) children were treated by private provider, while 3121(47.9%) cases were referred for diagnosis and 2443(37.5%) were referred after diagnosis for treatment; among all the referred, 3812(68.5%) were sent for investigations to District TB Centre (NTP). This study showed that many private providers referred children suspected having TB to laboratories for further diagnosis, but the cases identified in these investigations were often not notified to the NTP. This problem could be resolved by strengthening the referral linkages between private health providers, NTP laboratories and treatment centres through capacity building and training of their staff.